Relating maturity levels in environmental management by adopting Green Supply Chain Management practices: Theoretical convergence and multiple case study - Marco-Ferreira, Antonio; Jabbour, Charbel José Chiappetta [UNESP] (FapUNIFESP (SciELO), 2019)
Although the thematic maturity levels of corporate environmental management and the adoption of Green Supply Chain Management (GSCM) practices are consolidating, they have passed through long ways disconnected, given that both have their genesis circumscribed to corporate sustainability. The aim of this qualitative study was to identify the relationship between GSCM practices and maturity levels of environmental management. Literature systematization was carried out dealing with the maturity levels of environmental management and the typology of GSCM practices to reach the study objective. The study was based on multiple cases studies from five different companies inserted in the production chains with high environmental impact: the sector of pesticides, the sector of batteries, and the sector of lead recycling. It was sought the characterization of a logical standard for the adoption of GSCM practices inherent to each maturity level in environmental management. The main results indicate that: at the reactive maturity level in environmental management, organizations adopt specific GSCM practices related to the imposition of legislation; at the preventive level of maturity, organizations adopt GSCM practices related to the return of investments and the reduction of operational costs; and at the proactive level of maturity, organizations tend to adopt practices related to product innovation and environmental communicational processes and practices, aiming to obtain competitive advantages always based on environmental management.
Keywords: Brazil; Environmental management maturity; Green supply chain management; Green supply chain management in levels of maturity